Steady and transient performance of a pump-turbine on an open-loop test rig: pump mode. (July 2018) - Hu, J H; Yang, J D; Zeng, W
Abstract: In order to study steady and transient characteristics of the pump turbine, a model pumped storage system was established in State Key Laboratory of Water Resources and Hydropower Engineering Science, Wuhan University. Different from typical closed-loop test rigs, this open-loop system has a constant upstream and downstream water level, two parallel pump-turbines, surge tank, power grids, etc., to achieve similar operating modes as in prototype power station. This paper aims to investigate the pump performance of the pumpturbine unit, including steady state and transient state. The structure of the present paper is organized as follows: 1) Steady pump performance of a model pump-turbine under three guide vane openings (GVO) was obtained by point-by-point measurements with the the adjustment of spherical valve; Meanwhile, the source of steady hysteresis as well as hump instabilities was identified by pressure analysis. It was found that the pressure instabilities in draft tube caused the drop in the energy performance curve as well as the hysteresis. 2) By dynamically adjusting the opening of the spherical valve, performance curves from nominal flow discharge to zero discharge were obtained under a constant GVO. The results showed that the performance curves of the torque and the efficiency could be measured in a quasi-steady way with sufficient switch time of the spherical valve, despite a clear dynamic loop of the energy performance curves. 3) The performance curves of a model pump-turbine were extended from high flow discharge region to nominal flow discharge operating point through a transient experiment in which the head varied.